Studi Numerik Pengaruh Sudut Kemiringan Sudu Terhadap Performa Turbin Angin Vertikal Tipe Savonius - Masykur Masykur; Andre Kurniadi; Maidi Saputra; Murhaban Murhaban (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2021)
AbstractWind energy is a renewable energy source that can be felt in everyday life. To convert wind energy into electrical energy, a tool is needed that is a wind turbine. Horizontal Axis Wind Turbine is more widely used and developed today than the vertical type wind turbine. However, the vertical turbine has several advantages compared to the horizontal wind turbine, which is that it can move without depending on the direction of the wind. This study aims to determine the effect of tilt angel of savonius turbine with blades angle 30°, 60° and 90° the turbine power coefficient and determine the optimal turbine blade results in designing a Vertical wind turbine  by simulation  using Computational  Fluid Dynamics  (CFD). The variations used are tilt angel turbine blades is 30°, 60°, 90°. The results showed that the value of Cp (Power Coefficient) of wind turbines with the addition of the blade angel 30°, 60° and 90° had a different increase. The variation the addition of turbine blade tilt angle with 90° tilt angle can increase the efficiency of the turbine blade when compared 30°, 60° blade inclination this is evidenced by wind turbine speed contour analysis, wind vortex contour analysis and turbulence intensity contour analysis shows that the turbine blade simulation results with a slope of 90° has an efficient turbine blade that is very good and effective and get optimal results.Keywords:  Wind  turbine,  VAWT,  CFD,  Efficiency,  Contour,  Optimal,  TSR, power